Wherever you go in the Aegean, you are in Greek lands - Irene Kamberidou (SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S), no. 45 October 1986: 12-13., 1986)
Kamberidou, Irene (1986). Wherever you go in the Aegean, you are in Greek lands. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 45 October 1986: 12-13.  [reprinted from my Greek article in the daily AVGI). [Google scholar]  Αναλυτικότερα,  Στο SPOTLIGHT, όπως και στο περιοδικό ΑΤΗΕΝΑ Magazine, Monthly Review of Current Affairs, Publication of the International Studies Association, (1986-1987)—που ήταν εκδόσεις της Υπηρεσίας Ενημέρωσης του Υπουργείου Εξωτερικών (ΥΠΕΞ)— συμμετείχα στην αρθρογραφία με θεματολογία «Ελληνικός Πολιτισμός» και  «Ελληνική Κοινωνία», ως αποσπασμένη/με διάθεση από τη Γενική Γραμματεία Τύπου και Πληροφοριών (ΓΓΤΠ) στο ΥΠΕΞ.  (Δείγματα των άρθρων έχουν συμπεριληφθεί στα πρώτο μου βιογραφικά στο ΤΕΦΑΑ, για την εκλογή μου στη θέση ΕΕΠ, στη βαθμίδα του Λέκτορα και στη βαθμίδα του Επίκουρου). Επιπροσθέτως, στο SPOTLIGHT, publication of the Institute of Political Studies (I.P.S),   καθιέρωσα και ανέλαβα τη σελίδα  “Γυναικεία Θέματα”.  Ενδεικτικά αναφέρω και επισυνάπτω τα ακόλουθα άρθρα: Kamberidou, Irene (1984). Greek women now have an equal voice. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 1, May 18, 1984: 2.    Kamberidou, Irene (1984). The Greek farm woman, a first-class citizen. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 7, August 15, 1984: 3.  Kamberidou, Irene (1984). The Protection of Motherhood. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 8, Sept. 15, 1984: 8. Kamberidou, Irene (1984). Women at the Wheel. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no.  9, Oct. 1, 1984. Kamberidou, Irene (1984). The Protection of the Family, SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 10, Oct. 15, 1984.  Kamberidou, Irene (1984). Sport for Women means Life. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no.  13, Dec. 1, 1984: 8.  Kamberidou, Irene (1985). World Conference on Women in Nairobi. “New Strategies for Women’s Studies”. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 17, Feb. 1, 1985: 8.  Kamberidou, Irene (1985). Women Discuss Mass Media Image. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 31,  Nov. 15, 1985 Kamberidou, Irene (1985). Geraldine Ferraro, former vice-presidential candidate. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no.  32, Dec. 1, 1985:8. Kamberidou, Irene (1986). Aegean women organize study program. SPOTLIGHT, a fortnightly publication for political studies, publication of the Institute of Political Studies (I.P.S),  no. 34, January 1. 1986: 8.